Distributed optimization method for multi-area integrated energy systems considering demand response - Bai, Xuetao; Liu, Liu; Ju, Jiehua; Zhong, Xiaoyi; Zhou, Yuting; Lin, Jian; Huang, Yuan; Wu, Nianyuan; Xie, Shan; Zhao, Yingru (Frontiers in Energy Research, 2022)
Modern urban integrated energy systems are usually large in scale and consist of several subsystems located in different areas with various types of users. The design and operation optimization of multi-area integrated energy systems (IES) faces challenges in integrating user engagement, operational independence of subsystems, and the combination of long-term objectives and operation optimization. To solve these problems, the present study proposes a supply-demand coordinated optimization method for multi-area IES to balance the long-term overall objectives with the independence of participants such as users and subsystems. Increasing overall benefits and ensuring fairness can be achieved by using the proposed methods. In the case study, considering long-term objectives, the carbon emissions of the system operation are reduced by 9.43% compared to the case without the long-term objectives. Meanwhile, the results show an approximately 25% reduction in the total cost and a 65% reduction in carbon emission, compared to the baseline. Moreover, the cost of different users decreases by 13-17% from the baseline at the optimal agreed price. This optimization method provides a holistic framework for the design and operation, supply-demand coordination, and pricing of transactions for multi-area IES involving long-term planning and construction with multiple interests.